PEACE EDUCATION BASED ON LOCAL WISDOM OF PELA GANDONG IN SOCIAL SCIENCE - Anju Nofarof Hasudungan (Faculty of Social and Political Sciences University of Bangka Belitung, 2020)
The post-conflict recovery effort in Ambon, Maluku, which was the largest civil conflict after the collapse of the New Order, was not only needed by the survivors of the conflict. But also by the generation that did not experience the bloody conflict. Like students in SMPN 9 Ambon City and SMPN 4 Salahutu Liang Central Maluku who are the next generation of Maluku and of course who will maintain Ambon peace in the future. The purpose of this study is to describe how Social Science Education integrated the value of peace education based on local wisdom pela gandong. This research was conducted in January 2018 and continued in November 2019. The research method uses descriptive qualitative case study approach. Data collection was carried out by means of literature study, interviews, participatory observation, and document analysis. The results showed, with the existence of social conflict material in Social Science Education which was then integrated with Ambon conflict material and peace education based on Pela Gandong. Thus, students have improved both in terms of knowledge, skills and attitudes in understanding conflict and peace education through Social Science Education. At the same time cut off the trauma, mutual suspicion and hatred experienced by students so far.